Rhodium‐Catalyzed Alkene Difunctionalization with Nitrenes. Issue 27 (3rd June 2016) - Ciesielski, Jennifer; Dequirez, Geoffroy; Retailleau, Pascal; Gandon, Vincent; Dauban, Philippe
Abstract: The Rh II ‐catalyzed oxyamination and diamination of alkenes generate 1, 2‐amino alcohols and 1, 2‐diamines, respectively, in good to excellent yields and with complete regiocontrol. In the case of diamination, the intramolecular reaction provides an efficient method for the preparation of pyrrolidines, and the intermolecular reaction produces vicinal amines with orthogonal protecting groups. These alkene difunctionalizations proceed by aziridination followed by nucleophilic ring opening induced by an Rh‐bound nitrene generated in situ, details of which were uncovered by both experimental and theoretical studies. In particular, DFT calculations show that the nitrogen atom of the putative [Rh]2 =NR metallanitrene intermediate is electrophilic and support an aziridine activation pathway by N⋅⋅⋅ N=[Rh]2 bond formation, in addition to the N⋅⋅⋅ [Rh]2 =NR coordination mode. Abstract : Olefins difunctionalized : The Rh II ‐catalyzed oxyamination and diamination of aromatic and aliphatic alkenes generates 1, 2‐amino alcohols and 1, 2‐diamines in high yield with complete regiocontrol. The mechanistic details of these reactions were uncovered by means of both experimental and theoretical results, which revealed a Lewis acidic role of an Rh‐bond nitrene intermediate (see scheme).